(untitled) (Carte Romanze, 2021)
The article offers an introductory comparison between medieval metrological treatises and collections of recipes, both in Latin and in vernacular, and similar texts from Greco-Roman Antiquity, preserved by manuscript tradition or on papyrus, with a special focus on the unit of measurement of liquid capacity utilized in medical contexts. It will highlight analogies at linguistic (in the names used for the measures), theoretical (in the definition and quantification of the measures), and practical (in the awareness of several issues of standardization) levels, which attest to a real continuity of “measuring medicine” that is still effective nowadays.